ANALISIS PEMENUHAN KEBUTUHAN EKONOMI RUMAH TANGGA PETANI KENTANG DI DESA TOSARI KECAMATAN TOSARI KABUPATEN PASURUAN - Utomo, Dimas Puji; Yuliati, Nuriah; Syah, Mirza Andrian (Universitas Nusa Cendana, 2024)
The selling price of potatoes fluctuated, and the rising production input costs affected income, leading farmers to work in off-farm and non-farm sectors to meet household economic needs. The research aimed to analyze potato farming income as well as total household income and expenditures. The sampling method used purposive sampling, with a total of 60 respondents. This study employed income analysis and descriptive analysis. The results showed that the income from potato farming was Rp13,465,899.12 per planting season. The total household income of the farmers was Rp20,993,565.78 over four months, consisting of on-farm, off-farm, and non-farm income sources. Household expenditures amounted to Rp7,116,555.56, which included food and non-food expenses. Keywords: Farming; Income Analysis; Farmers' Households